Hubungan Antara Persepsi Guru Terhadap ProgramSertifikasi, Motivasi Kerja, Iklim Sekolah DenganKinerja Guru - Winarno, Sapto (2011)
This research aim to know and analyze the relation of: (1) perception learn to certification program, job motivate of the teacher, school of climate, with the teacher performance, (2) work motivation of the teacher, school of climate, with the teacher performance, (3) school of climate, with the teacher performance, in SMPN I of Mojogedang, Mojogedang District of Karanganyar Sub-Province. This research is including quantitative research. Population in this research is teacher of SMPN I of Mojogedang, Mojogedang District of Karanganyar Sub- Province, a number of 64 people learn, all population member made by sample of research or population research. Appliance of data collecting used with the documentation and use the questioner. The analyze technique data conducted with the doubled linear regression. Results of the research are: (1) there are relation which significant between perception Learn to certification program, job motivate of the teacher, school of climate, with the teacher performance in SMPN I of Mojogedang, Mojogedang District of Karanganyar Sub-Province. Analyze result of correlation r = 0,638; P- x1y value = 0,000 < 0,01, meaning hypothesis raised to be accepted, there is relation which are positive. (2) total of independent variable (X) can explain the variable dependent (Y) of equal to 63,8%. Excelsior of perception support learns to certification program, jobs motivate of the teacher, school of climate, hence excelsior of teacher performance. (3) level of coefficient of determinacy or R square = 0,545 meaning that influence from independent variable of perception Learn to certification program, job motivate of the teacher, school of climate equal to 54,5 %, and influence there is still from other factors outside this variable independent research that is equal to 100 - 54,5 = 45,5 %.